Návrh strategie firmy - Dubnický, Peter (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Podnikání v oboru IT se za poslední léta poměrně výrazně mění. Společnost M Computers s.r.o., podnikající převážně v oblasti prodeje hardware dnes stojí před rozhodnutím, jak na dané změny reagovat a zvýšit tak svou konkurenceschopnost. Cílem předkládané diplomové práce je pomocí metod strategické analýzy prozkoumat současnou pozici společnosti, závěry analýz relevantně zhodnotit a stanovit návrh strategie firmy do roku 2009.

The IT business has dramatically changed within last few years. Nowadays M Computers ltd. established mainly as a hardware reseller is being faced with a decision about the answer to these changes and further direction of the business to gain the competitive advantage. The goal of presented master`s thesis is to analyze and evaluate the current position of the company using the methods of strategic analysis. Furthermore a proposal of company strategy by the year 2009 will be provided.
Proposal of Company Strategy
Keywords: strategie; firma; konkurence; analýza; mise; organizační jednotka; IT; strategy; company; competition; analysis; mission statement; organizational unit; IT